Application of response surface methodology for parameters optimization in hot pressing kenaf reinforced biocomposites / Izdihar Tharazi... [et al.] - Tharazi, Izdihar; Sulong, Abu Bakar; Mohd Salleh, Farrahshaida (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
on the mechanical properties of the final product. Typically, the most important processing parameters are temperature, heating time and pressure but there are cases where more or fewer parameters are involved depending on the type of the materials, fabrication techniques including the capabilities of the processing equipment. The traditional approach in experimental work is costly and time consuming due to evaluation of multiple dependent variables. In this paper, design of experiments (DOE) technique based on statistical analysis has been employed to optimize hot press parameters on tensile properties of unidirectional kenaf fibres reinforced polylactic-acid (PLA) composite. The kenaf/PLA composite samples were fabricated using hot press method by stacking the aligned kenaf fibres with the PLA films. The stacked materials were hot pressed at varying processing parameters specifically the temperature, pressure and heating time. The Box-Behnken Design (BBD) through Response Surface Methodology (RSM) was employed to identify the cause and effect of relationship between the processing parameters with the composite’s tensile strength and Young’s modulus. Results from ANOVA showed that all three parameters and interactions significantly affect the composite’s tensile strength. For Young’s modulus, pressure and heating time are the significant parameters. Optimal processing parameters for composite fabrication for optimum tensile properties are at 200 MPa, 3MPa and 7 minutes.